Fashion - Foreworded by Tabberer, Maggiet (Sydney Murdoch Books, 2005)
Is a collection of fashion stills taken from the Cinesound and Movietone newsreels, which played in Australian cinemas from 1931 to 1975. Featured are Jean Shrimpton's scandalous appearance, hatless and bare-legged, at Melbourne's Derby Day in 1965; Maggie Tabberer modelling; and top mannequins in parades of French couture.
Include Illustrations and Index
Essays by Robinson, Felicity
Keywords: Australia -- Costume -- Fashion